Index Model in Analytic Design of Proft from Sales - T. A. Pantina; M. A. Rastov (Учёт. Анализ. Аудит)
Analytical design is the concept of designing a sequence of analytical procedures that ensures the use of all the possibilities of fnding ways and identifying key areas for improving the business. The article is devoted to the issues of eliminating fragmentation and standardization of analytical research of sales profts as an indicator of systemic problems of business effcien cy. The methodological basis of the study is the concept of analytical design with a focus on designing such a sequence of analytical procedures, which ensures the proper study of the causal relationships that determine the change in the indicator under study. The method uses a numerical sales proft model, presented using medium-sized index systems and multiplier-additive calculations that provide a link between the calculation of relative and absolute changes in the study of their signifcant factors, such as the proftability and sales volumes of certain types of products, as well as the ratios between them. It is concluded that the index method is key in the variety of products, numerous customers, markets and distribution channels of the company. Incorporating the developed index model intoa standardized analytical sales proft design signifcantly enhances the ability to optimize the range of goods (servicesand redistribute priorities in customer relationships, allowing to form a system of key performance indicators to monitorthe business performance of the employees, departments and the organization as a whole.